Facing Challenges in Achieving Clean Government: A Public Administration Perspective - Rahman, Fatmawati A; Rifdan, Rifdan; Nasruddin, Nasruddin; Jusriadi, A; Agus, Muhammad (Program Pascasarjana Universitas Negeri Makassar, 2024)
Clean government or good governance is an important concept in public administration aimed at enhancing the quality of public services, improving government-citizen relations, and building public trust in government institutions. Implementing the principles of transparency, accountability, and public participation is essential to reduce corruption, increase bureaucratic efficiency, and encourage citizen involvement in government decision-making. Transparency provides citizens with clear access to information regarding decision-making processes and public policies. Accountability ensures that public officials are held responsible for their actions, while public participation enables citizens to take an active role in policy-making. However, several challenges hinder the implementation of clean government, including weak institutions, a lack of transparency and accountability, and limitations in infrastructure and human resources. Information and Communication Technology (ICT) holds potential to support clean governance by enhancing transparency and expediting administrative processes. Nonetheless, technology implementation is often constrained by inadequate infrastructure. Additionally, low public participation worsens policy quality. Achieving clean government requires institutional reform, strengthening transparency and accountability, and utilizing appropriate technology, supported by active public involvement in every aspect of governance